2012
DOI: 10.1111/j.1447-0756.2012.01847.x
|View full text |Cite
|
Sign up to set email alerts
|

Endocervical glandular involvement, positive endocervical surgical margin and multicentricity are more often associated with high‐grade than low‐grade squamous intraepithelial lesion

Abstract: The current study showed that EGI, positive ESM and multicentricity were more often associated with HSIL/CIN II + III than with LSIL/CIN I. Moreover, the frequencies of EGI, multicentricity, and positive ESM increased with increasing severity of the cervical lesion. This result may influence the preference for the type of surgical procedure used for patients with cytological diagnosis of HSIL.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
7
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(10 citation statements)
references
References 25 publications
3
7
0
Order By: Relevance
“…Endocervical glandular involvement was reported to be 4 times more common in high-grade CIN when compared with low-grade CIN [6]. Results of Kır et al [5] was similar to ours, 25% endocervical glandular involvement in CIN 1 and 91% endocervical glandular involvement in CIN 3. Previously reported studies related endocervical glandular involvement to higher recurrence after LEEP [2,[8][9][10][11][12].…”
Section: Discussionsupporting
confidence: 89%
See 2 more Smart Citations
“…Endocervical glandular involvement was reported to be 4 times more common in high-grade CIN when compared with low-grade CIN [6]. Results of Kır et al [5] was similar to ours, 25% endocervical glandular involvement in CIN 1 and 91% endocervical glandular involvement in CIN 3. Previously reported studies related endocervical glandular involvement to higher recurrence after LEEP [2,[8][9][10][11][12].…”
Section: Discussionsupporting
confidence: 89%
“…Previously, another study designed similar to ours also reported higher multicentricity in high-grade CIN [5]. Other studies searched recurrence rates in multicentric lesions and related multicentircity to higher recurrence [2].…”
Section: Discussionmentioning
confidence: 62%
See 1 more Smart Citation
“…Kodampur et al, 16 in a cohort study of 309 women with highgrade CIN who underwent LEEP, confirmed the increased need for further intervention when there was endocervical glandular involvement (p ¼ 0.024), which is similar to our findings. Glandular involvement is closely related to HSIL, 17 and it was positively related to recurrence in the samples (p ¼ 0.019), which corroborates the findings of Güdücü et al, 18 who observed that glandular extension is more present in HG lesions, thus demanding greater care when monitoring these cases.…”
Section: Discussionsupporting
confidence: 86%
“…Margin status (endocervical, ectocervical) were defined as positive based on the presence of AIS, invasive carcinoma or less than 1 mm at the edge of the specimens, or on the presence of CIN or less than 0.1 mm. Endocervical glandular involvement was defined as dysplastic squamous epithelium occupying well-circumscribed, rounded spaces in the depth of the cervical stroma 20 .…”
Section: Methodsmentioning
confidence: 99%